Effectiveness of laparoscopic niche resection versus expectant management in patients with unexplained infertility and a large uterine caesarean scar defect (uterine niche): protocol for a randomised controlled trial (the LAPRES study) - Ben W Mol; Judith A F Huirne; Wouter J K Hehenkamp; Rik van Eekelen; Jolijn Vissers; Saskia J M Klein Meuleman; Robert A de Leeuw; Freek A Groenman (BMJ Open, 2023)
Introduction A uterine niche is a defect at the site of the uterine caesarean scar that is associated with gynaecological symptoms and infertility. Promising results are reported in cohort studies after a laparoscopic niche resection concerning reduction of gynaecological symptoms in relation to baseline and concerning pregnancy outcomes. However, randomised controlled trials to study the effect of a laparoscopic niche resection on reproductive outcomes in infertile women are lacking. This study will answer the question if laparoscopic niche resection in comparison to expectant management improves reproductive outcomes in infertile women with a large uterine niche.Methods and analysis The LAPRES study is a randomised, non-blinded, controlled trial, including 200 infertile women with a total follow-up of 2 years. Women with the presence of a large niche in the uterine caesarean scar and unexplained infertility of at least 1 year or failed IVF will be randomly allocated to a laparoscopic niche resection within 6 weeks or to expectant management for at least 9 months. A large niche is defined as a niche with a depth of >50% of the myometrial thickness and a residual myometrium of ≤3 mm on transvaginal ultrasound. Those receiving expectant management will be allowed to receive fertility therapies, including assisted reproductive techniques, if indicated. The primary outcome is time to ongoing pregnancy, defined as a viable intrauterine pregnancy at 12 weeks’ gestation. Secondary outcome measures are time to conception leading to a live birth, other pregnancy outcomes, received fertility therapies after randomisation, menstruation characteristics, patient satisfaction, quality of life, additional interventions, and surgical and ultrasound outcomes (intervention group). Questionnaires will be filled out at baseline, 6, 12 and 24 months after randomisation. Ultrasound evaluation will be performed at baseline and at 3 months after surgery.Ethics and dissemination The study protocol was approved by the medical ethics committee of the Amsterdam University Medical Centre. (Ref. No. 2017.030). Participants will sign a written informed consent before participation. The results of this study will be submitted to a peer-reviewed journal for publication.Trial registration number: Dutch Trial Register (ref. no. NL6350 http://www.trialregister.nl).